Fluorescence/luminescence-based markers for the assessment of Schistosoma mansoni schistosomula drug assays. Issue 1 (December 2015) - Panic, Gordana; Flores, Dayana; Ingram-Sieber, Katrin; Keiser, Jennifer
Abstract Background Schistosomiasis is responsible for a tremendous public health burden, yet only a single drug, praziquantel, is available. New antischistosomal treatments should therefore be developed. The accuracy, speed and objectivity ofin vitro drug screening depend on the assay read-out. Microscopy is still the current gold standard and is in need of updating to an automated format. The aim of the present study was to investigate a panel of fluorescence/luminescence dyes for their applicability as viability markers in drug sensitivity assays forSchistosoma mansoni schistosomula. Methods A search for available viability and cytotoxicity marker assays and dyes was carried out and a short-list of the most interesting candidates was created. The selected kits and dyes were tested onS. mansoni Newly Transformed Schistosomula (NTS), first to assess whether they correlate with parasite viability, with comparatively low background noise, and to optimise assay conditions. Markers fulfilling these criteria were then tested in a dose–response drug assay using standard and experimental drugs and those for which an IC50 value could be accurately and reproducibly calculated were also tested on a subset of a compound library to determine their hit-identification accuracy. Results Of the 11 markers selected for testing, resazurin, Vybrant® and CellTiter-Glo® correlated best with NTS viability, produced signals ≥ 3-fold stronger than background noise and revealed a significant signal-to-NTS concentration relationship. Of these, CellTiter-Glo® could be used to accurately determine IC50 values for antischistosomals. Use of CellTiter-Glo® in a compound subset screen identified 100 % of hits that were identified using standard microscopic evaluation. Conclusion This study presents a comprehensive overview of the utility of colorimetric markers in drug screening. Our study demonstrates that it is difficult to develop a simple, cheap "just add" colorimetric marker-based drug assay for the larval stage ofS. mansoni. CellTiter-Glo® can likely be used for endpoint go/no go screens and potentially for drug dose–response studies.